Control over Compliance with International Law - Butler, William E., (International Law - Book Archive pre-2000., 1991)
Of all the Issues on the East-West agenda, none is more vital to the perestroika processes on the international plane than confidence on all sides that international legal obligations assumed will be wholly complied with. Increasingly such confidence requires particular often intrusive, machinery to ensure compliance to the satisfaction of the parties concerned. The revolution under perestroika is that, in East-West relations, the former protagnosts now accept that machinery is required, and the deliberations have moved onto the level of why, how much, and how it can best be accomplished. The contributions to the present volume, continuing and developing earlier Anglo-Soviet symposia on public international law, addresses the topic for the first time in a framework that transcends arms control and disarmament.